2017
DOI: 10.5507/euj.2017.004
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental movement skill and physical fitness measures in children with disabilities

Abstract: This study aimed to explore fundamental motor skills and physical fitness outcomes in the group of children with visual, physical and intellectual disabilities. Alongside the average data outcomes, possible gender differences in all measures were also explored. In addition, the association between the level of movement performance and physical fitness variables was investigated. Participants were 82 elementary school age children with mild to moderate disabilities (mean age 9.6 years). To assess fundamental mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
0
7
0
1
Order By: Relevance
“…Finally, this study shows that adolescent with spina bifida and cerebral palsy can meet ACSM guidelines for level of activity by participating in WCB. The addition of testing fundamental movement skills and physical fitness measures could be utilized to obtain overall health related and skill related measures for each player (Klavina, Ostrovska, & Campa, 2017;Temple, Alston, Elder& Stuart-Hill, 2019). Furthermore, studies could incorporate measurements to assess youth WCB players quality of life and how it affected by being involved with this particular sport (Feter, Calonego, Cavanhi & del Vecchio, 2018).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Finally, this study shows that adolescent with spina bifida and cerebral palsy can meet ACSM guidelines for level of activity by participating in WCB. The addition of testing fundamental movement skills and physical fitness measures could be utilized to obtain overall health related and skill related measures for each player (Klavina, Ostrovska, & Campa, 2017;Temple, Alston, Elder& Stuart-Hill, 2019). Furthermore, studies could incorporate measurements to assess youth WCB players quality of life and how it affected by being involved with this particular sport (Feter, Calonego, Cavanhi & del Vecchio, 2018).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…The performance tasks consisted of jumping, running, rhythm, overhand throwing, kicking, gymnastic, and imitation activities. Previous studies determined that the level of motor skill performance and physical fitness had a significant relationship among children with [ 48 , 49 ] and without disabilities [ 50 , 51 ]. This implied physical activity interventions could influence both motor skill competency and physical fitness in children with and without disabilities.…”
Section: Methodsmentioning
confidence: 99%
“…In physical disability children, some studies have found worse motor performance than typical developing children, 41,42 and positive effects of motor intervention programs. 43,44 Children with intellectual disability have presented worse performance than typically developing children, [45][46][47] with better performance to children that attended interventions, 47 as well as better performance of children with mild level than moderate or severe levels of disability. [48][49][50] Children with autism spectrum disorder presented fundamental skills performance below average due to poor communicative skills, 51,52,53 or to a sensorial dysregulation specific to this disorder.…”
Section: Fundamental Motor Skillsmentioning
confidence: 99%